The Effect Of Health Cadre Motivation on Performance in Efforts to Improve Toddler Growth: Meta Analysis: The Effect Of Health Cadre Motivation on Performance in Efforts to Improve Toddler Growth: Meta Analysis - Akhyar, Muhammad; Rahmawati, Anita; Setyowati, Retno; Mulyani, Sri (Mulawarman International Conference on Tropical Public Health, 2025)
Health cadres are the spearhead in implementing health programs at the village level. In the context of toddler growth, cadre duties include monitoring child growth and development and early detection of toddler health problems. Cadre motivation is seen as a factor that influences how much involvement and dedication cadres have in carrying out their duties well. This article aims to analyze the influence of health cadre motivation on performance in efforts to improve toddler growth. This study is a meta-analysis using the PRISMA flowchart and PICO model. Population: toddler health cadres. Intervention: have good motivation. Comparison: poor motivation, Outcome: Cadre performance. The process of searching for articles by searching through databases in Google scholar, Scopus, ProQuest, PubMed, Elsevier, and Science directly. The keywords used are "health cadre motivation" OR "health cadre performance" OR "toddler growth" OR "toddler growth efforts" AND "health cadre efforts" AND "Cross sectional" AND "aOR". Articles were selected based on inclusion criteria, namely articles with a cross-sectional design published in 2015-2024 analyzed using logistic regression. Data were analyzed using Review Manager 5.3. Meta-analysis was conducted on 7 primary studies from countriesEthiopia, Nigeria, and Indonesia. The results showed that health cadre motivation improved cadre performance in toddler growth (aOR= 1.84; 95% CI= 1.45 to 2.33; p=0.02). Good motivation of health cadres improves the performance of cadres in efforts to grow toddlers.